Thoracic surgery in solving enormous elevation of the left hemidiaphragm - Cvijanović Vlado; Stanić Vojkan; Ristanović Aleksandar; Gulić Bojan; Durković Savo; Stamenović Davor; Marić Nebojša; Kovačević Snežana (Vojnosanitetski Pregled)
Background. Acquired elevation of the diaphragm is mostly the result of phrenic nerve paralysis, some of thoracic and abdominal patological states, and also some of neuromuscular diseases. Surgical treatment is rarely performed and is indicated when lung compression produces disabilitating dyspnea, and includes plication of diaphragm. The goal of this case report has been to show completely documented diagnostic procedures and surgical treatment one of rare pathological condition. Case report. A 62-year-old patient was admitted to our clinic because of surgical treatment of the enormous elevation of the left hemidiaphragm. After thoracotomy and plication of the bulging diaphragm, lung compression did not exist any more and mediastinum went back in the normal position. Conclusion. Elevation of the diaphragm rarely demands surgical correction. When it is complicated with lung compression and disabilitating dyspnea, surgical treatment has extremely useful functional effect.